Estetika Busana dan Gerak dalam Tari Kidung Lereng Rahtawu sebagai Representasi Budaya Muria Kudus - Arfiasya Husna Zakiyya; Wasis Wijayanto (YASIN, 2026)
The Kidung Lereng Rahtawu dance is a cultural tradition of communities living on the slopes of the Muria Mountain Range in Kudus, representing local cultural identity amid ongoing social and cultural change. Although traditional dance is increasingly recognized as important for strengthening local identity, studies that specifically examine the aesthetic values of costume constructed from arrangements of used-fabric motifs, movement aesthetics, and the representation of Muria Kudus culture in the Kidung Lereng Rahtawu dance remain limited. This study aims to examine the aesthetic values produced by the composition of interwoven motifs of discarded fabrics into new costumes, to analyze the movement aesthetics of the Kidung Lereng Rahtawu dance, and to explain the representation of Muria Kudus culture in this dance. Using a case study approach with qualitative methods, data were obtained through observation, interviews, and documentation of the process of creating dance costumes, the implementation of performances, and their supporting cultural context. The findings show that the costume and movement aesthetics of the Kidung Lereng Rahtawu dance reflect the values of simplicity, religiosity, and local wisdom of the Muria community; its costumes combine natural color elements with spiritual symbols, while its movements represent a harmonious relationship between humans, nature, and God. These findings affirm that the Kidung Lereng Rahtawu dance functions as a representation of local cultural identity that must be preserved, while also contributing to the development of dance studies, particularly those related to costume and movement aesthetics as expressions of local culture.